Evaluating 3R waste management practice for construction and demolition waste among contractors in Malaysia - Abd Rahim, Muhammad Aminullah; Ghazali, Siti Aisyah; Mohd Zahid, Azyan Zafyrah; Dzulkafli, Noor Fazreen; Kassim, Jalina (Faculty of Civil Engineering, 2025)
This study investigates the implementation of the 3R (Reduce, Reuse, Recycle) principles in reducing construction waste among contractors in Malaysia. Given that the construction industry is substantial contribute to environmental degradation thereby effective waste management for sustainable development is warranted. Therefore, the present study aims to identify the key materials contributing to construction waste, examine influencing factors, and assess contractor awareness related to 3R practices adoption. For this, a quantitative approach through Likert-scale questionnaire distributed via Google Forms to contractors across various regions and company grades in Malaysia was used. The questionnaire comprised seven sections covering background information, waste materials, contributing factors, 3R awareness, current practices, barriers, and perceived benefits. A total of 33 valid responses were analysed using descriptive statistics in Microsoft Excel. Results showed that concrete and aggregates were the highest contributors to construction waste (mean value = 3.58), followed by wood and ceramics. Furthermore, the respondents demonstrated a strong awareness of 3R principles (mean = 4.15) and environmental impacts of waste, but moderate familiarity with relevant policies and sustainable construction practices. For instance, the major 3R implementation barriers included limited knowledge, lack of training, and inadequate waste management resources. Despite these challenges, respondents acknowledged the environmental (mean = 4.58), economic, and social benefits of 3R practices, such as reducing landfill use, improving profitability, and enhancing public perception. The study concludes that increasing education, training, and policy support is vital to improve 3R adoption among contractors, thereby promoting more sustainable construction practices in Malaysia.